High-Efficiency Solution-Processed Inorganic Metal Halide Perovskite Light-Emitting Diodes - Cho, Himchan (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.